2008
DOI: 10.1007/s10460-008-9154-9
|View full text |Cite
|
Sign up to set email alerts
|

Devon Acres CSA: local struggles in a global food system

Abstract: This paper focuses on examining the dynamic nature of community supported agriculture (CSA) and the real-world experiences which mark its contours, often making it distinct from the early idealized CSA ''model.'' Specifically, our study examines the narratives of the farmers of Devon Acres CSA over its duration, in tandem with a survey of recent shareholders in order to understand and explain its evolution. The framework we develop here shows that this CSA is largely characterized by instrumental and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 30 publications
6
92
0
8
Order By: Relevance
“…The high dependence of CSA on having a high rate of retention of a core group of engaged consumers shows the fragility of this model of food provision [98,99]. In addition, the CSA model provides no per se economic benefits for farmers.…”
Section: Community Supported Agriculture (Csa)mentioning
confidence: 99%
See 1 more Smart Citation
“…The high dependence of CSA on having a high rate of retention of a core group of engaged consumers shows the fragility of this model of food provision [98,99]. In addition, the CSA model provides no per se economic benefits for farmers.…”
Section: Community Supported Agriculture (Csa)mentioning
confidence: 99%
“…They also offer environmental education and contribute to awareness regarding origin, quality, and seasonality of food, which can lead to behavioural and attitude changes in consumers, such as sustainable consumption [72,97,101]. According to some authors, these changes might finally initiate the transformation of the existing food and economic system [98,102,103].…”
Section: Community Supported Agriculture (Csa)mentioning
confidence: 99%
“…Research in California found that many farmers' market and CSA managers prioritized food security for low-income people and used strategies to try to meet the needs of low-income consumers (Guthman, Morris, & Allen, 2006). CSAs vary in their structures and business models, including size, cost of membership, growing methods, member involvement and the food that they provide (Feagan & Henderson, 2008;Lang, 2010;Martinez et al, 2010;Schnell, 2007). Since CSAs are highly local creations, they attempt to forge relationships between consumers and farmers that reflect unique conditions and needs (Groh & McFadden, 1997).…”
Section: Community Supported Agriculturementioning
confidence: 99%
“…Producers promise to use organic or similarly alternative production methods to produce and regularly supply fresh foods to consumers. It is an agricultural development model emphasizing communication, interaction, and mutual trust between producers and consumers as well as social and ecological sustainability [33][34][35][36]. Compared with other sale models, CSA alleviates the problem of information asymmetry in the green agricultural product market to a certain extent.…”
Section: Research On the Cooperation Between Producers And Consumers mentioning
confidence: 99%